The effects of minimum-wage increases on wage offers, wage premiums and employee effort under incomplete contracts - Brink, William; Kuang, Xi (Jason); Majerczyk, Michael (Accounting, Organizations and Society, 2021)
We experimentally investigate how increases in legally required minimum wages affect wage offers, wage premiums (i.e., the excess of wages over the minimum wage), and employee effort. Prior research has documented a gift-exchange relationship between firms and employees, whereby higher wage offers lead to higher effort. However, when the minimum wage increases, expectations regarding gift wages may also change. We predict that, following such a change, firms and employees will self-servingly determine their reference point for gift wages. As a result, while firms will increase wage offers, wage premiums will decline, and thus employees will not increase their effort. The results of (1) a laboratory experiment and (2) two online experiments are consistent with our predictions, suggesting that minimum-wage increases can have a negative effect on employee effort. Ultimately, employees respond to equivalent wages differently depending on the context surrounding the wage level. Implications for theory and practice are discussed.